Two new species of the genus Merulempista Roesler, 1967 from China (Lepidoptera, Pyralidae, Phycitinae) - Liu, Hongxia; Zhang, Xiuying; Li, Houhun (Zootaxa, 2022)
The genus Merulempista Roesler, 1967 is studied in China. Two new species Merulempista pectinata Liu and Li, sp. nov. and M. similirubriptera Liu and Li, sp. nov. are described. Images of adults and genitalia are provided, with a key to all known Chinese species.